Key Challenges for the Leader of a Strategic Business Network Operating in a Foreign Market - Hauke-Lopes, Aleksandra (Studia Oeconomica Posnaniensia, 2014)
The article presents selected aspects of a strategic network approach as an optimisation method for operating in a foreign service-market. The important tasks for the leading enterprise of a strategic network are considered to include concentrating on five areas: strategy, core competencies, relationships within the network, external environment, and people. These areas significantly affect the competitive position of the leading enterprise in a new market. The key challenges for the leading enterprise of a strategic business network in a foreign service-market include the implementation of the strategy (including the creation of an appropriate business model and the development of cooperation in the network) and the transfer of knowledge (enhancing the process and removing barriers to knowledge transfer in the network). In order to succeed in a new market, the leading enterprise of a strategic business network should be constantly active in both these key areas.